Introducing the Longitudinal Multi‐Agency Data Integration Project and Its Role in Understanding Income Dynamics in Australia. (1st December 2019) - Biddle, Nicholas; Breunig, Robert; Markham, Francis; Wokker, Chris
Abstract: The opening up of access to data from the Multi‐Agency Data Integration Project provides an opportunity to fill a number of research gaps on inequality in Australia. Our paper begins the external validation of these data, focusing on what the data can tell us about the distribution, dynamics and determinants of income in Australia. It has the potential to shed new light on these aspects, but the dataset should be used with caution, taking into account some key limitations, including incomplete linkage and more limited income information for those who do not complete a tax return.